The EFFECTS OF BIOCHAR DOSE AND MEDIA MOISTURE CONTENT ON THE GROWTH OF LOCAL EBAN COFFEE SEEDLINGS IN AGROFORESTRY SYSTEMS - Yakobus P.E. Saba Agu; Krisantus Tri Pambudi Raharjo; Robertus Anin (Fakultas Pertanian dan Bisnis Universitas Mahasaraswati Denpasar, 2026)
According to BPS data (2021), the North Central Timor Regency has a potential coffee production of 210.00 tons, with a planting area reaching nearly 1,152 ha, predominantly distributed in the West Miomaffo region. Water availability and soil fertility levels are the primary limiting factors in coffee cultivation practices. This study aims to determine the effect of biochar dosage and soil moisture levels on the growth of coffee seedlings (Coffea sp.). This research utilized a Split Plot Design with two factors and three replications. The results showed that a higher watering discharge significantly increased soil temperature. An application of 40 g of biochar significantly increased plant height at 84 DAP (Days after Planting) and stem diameter across all observation periods. While the combination of 60 g biochar and a watering discharge of 4 mL/second produced the tallest plants at each observation, the 40 g biochar dosage was sufficiently influential and not significantly different from the 60 g dosage across all watering levels. The application of biochar dosage is closely related to the increase in soil organic carbon content, which subsequently influences the increase in plant height, stem diameter at 70 DAP, and 84 DAP. The treatment of 60 g biochar and 4 mL/second watering was found to be the most optimal in enhancing the growth of coffee seedlings.